Indirect electrochemical cyclization of bromoalkoxylated derivatives mediated by nickel(II) complex in environmentally friendly medium - Duñach, E. (2008)
An improved procedure has been developed using a catalytic amount of a nickel(II) complex in the efficient and selective electrochemical cyclization of propargyloxy and allyloxy bromo derivatives into substituted tetrahydrofurans using ethanol and ethanol–water mixtures as environmental-friendly systems. The reduction of the substrates proceeded via one-electron cleavage of the carbon–bromine bond to form a radical-type intermediate that undergoes cyclization to afford the tetrahydrofuran structures in good yields.